PEMANFAATAN KERAJINAN GONGGONG SEBAGAI MEDIA PENINGKATAN KREATIVITAS DAN KETERAMPILAN IBU-IBU DESA BUSUNG DALAM MENDORONG PARIWISATA LOKAL - Salihi, Salihi; Hasnarika, Hasnarika; Afriyadi, Afriyadi; Fauzi, Fauzi; Tommy Munaf (JURNAL PENGABDIAN MANDIRI, 2025)
Busung Village is one of the tourist villages located in the Seri Kuala Lobam District, Bintan Regency, Riau Islands Province. The majority of its residents work as fishermen, totaling 163 people. To reduce the waste produced from gonggong (a type of sea snail), the local community can utilize the shells to create various handicrafts with marketable value. The main objective of this activity is to increase income, reduce waste, and stimulate the creativity of the women in Busung Village. This training was attended by seven women, all members of the KUBE group. The methods used in this activity include providing information on the economic value that can be gained from processing gonggong waste, as well as hands-on training in making keychains from gonggong shells. The outcome of this community service activity is the increased knowledge of the KUBE members in processing gonggong waste and their ability to independently create handicrafts.